4a-2ab-11a-7ab=

Simple and best practice solution for 4a-2ab-11a-7ab= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-2ab-11a-7ab= equation:


Simplifying
4a + -2ab + -11a + -7ab = 0

Reorder the terms:
4a + -11a + -2ab + -7ab = 0

Combine like terms: 4a + -11a = -7a
-7a + -2ab + -7ab = 0

Combine like terms: -2ab + -7ab = -9ab
-7a + -9ab = 0

Solving
-7a + -9ab = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '-1a'.
-1a(7 + 9b) = 0

Ignore the factor -1.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(7 + 9b)' equal to zero and attempt to solve: Simplifying 7 + 9b = 0 Solving 7 + 9b = 0 Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9b = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 9b = 0 + -7 9b = 0 + -7 Combine like terms: 0 + -7 = -7 9b = -7 Add '-9b' to each side of the equation. 9b + -9b = -7 + -9b Combine like terms: 9b + -9b = 0 0 = -7 + -9b Simplifying 0 = -7 + -9b The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

a = {0}

See similar equations:

| -4de+6de+11de+-4de= | | 4=0.8(y/6) | | 2(x+2)-8=3x-20 | | -4de+6de+11de-4de= | | (3x^5y^3/10x^3)(20x/12y^4) | | -2z^2-42z=0 | | 6x-4/7+x=9+5x/5+6 | | 5t+7t+2p+4p= | | x-0.09=2.22-0.01x | | 3.6(j+4)=1.4(16+j) | | 6-5[4-(6y-3)]= | | 3x^5y^3/10x^3x20x/12y^4 | | 4=-2(x)(x)+3 | | 10a+8(a-3)=15 | | 4=-2x+3 | | 2x+40-4x=1-7x+4 | | 1205(2w-13)=3(2w-5) | | 2ab*3+3xb*2-5b*4+2b*2= | | csquared-5c=0 | | 5n+6n^4-7n+15n^4+13n=x | | (5x-8)(x^2+9x-10)= | | 3x^4+12x^3-36x^2=0 | | 1.4-0.2x=3.2 | | 0.07+0.4x=2 | | 5n-1=2n+8 | | 3b-9-86=11 | | -3p+2=2p+12 | | 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 |

Equations solver categories